Retrospective case series describing the efficacy, safety and cost-effectiveness of a vial-sharing programme for canakinumab treatment for paediatric patients with cryopyrin-associated periodic syndrome - Abdulkadir A. Elmi; Karen Wynne; Iek L. Cheng; Despina Eleftheriou; Helen J. Lachmann; Philip N. Hawkins; Paul Brogan (BMC, 2019)
Abstract Background Cryopyrin-associated periodic syndrome (CAPS) is a rare autoinflammatory disease, caused by gain of function mutation in NLRP3 resulting in excess production of interleukin-1 (IL-1). Canakinumab is a human monoclonal antibody against Interleukin-1 beta (IL-1β), licensed for the treatment of CAPS. The objective of the study was to describe the feasibility and cost-effectiveness of a canakinumab vial-sharing programme for paediatric patients with CAPS. Method Retrospective case series and clinical service description of a national specially commissioned CAPS clinic at Great Ormond Street Hospital (GOSH). Effectiveness was assessed using a CAPS disease activity score (DAS) and serum amyloid A protein (SAA). Adverse events were collected to determine safety. The number of canakinumab vials saved was considered when investigating the cost-effectiveness of vial-sharing. Results Nineteen/20 (95%) of our paediatric patients achieved minimally active clinical disease activity with canakinumab monotherapy; and 75% achieved both minimally active clinical disease and serological remission using a pre-specified definition based on the CAPS DAS and SAA level. Canakinumab was well tolerated, with only one child developing an infection requiring hospitalisation during the study. Canakinumab vial sharing resulted in 117 vials of canakinumab saved over a 24-month period, equating to a direct drug-related cost saving of £1,385,821, and a conservative estimated 5-year cost-saving of £3,464,552.50. Conclusion We provide further evidence for the effectiveness and safety of canakinumab in children with CAPS, and highlight the cost-effectiveness of a vial-sharing programme for this high cost medicine. We suggest that this could have important implications for the delivery of other high cost medicines used in paediatric practice.